Hey all, any help proving the following summation would be greatly appreciated!

Σ from j=1 to k of j^2 = k(k+1)(2k+1) / 6

Thank you!

Printable View

- Feb 25th 2011, 03:16 PMjstarks44444Summation proof
Hey all, any help proving the following summation would be greatly appreciated!

Σ from j=1 to k of j^2 = k(k+1)(2k+1) / 6

Thank you! - Feb 25th 2011, 03:22 PMPlato
- Feb 26th 2011, 12:03 AMchisigma
See...

http://www.mathhelpforum.com/math-he...la-172620.html

... taking into account that is ...

Kind regards

- Feb 26th 2011, 12:08 AMProve It